HOW TO LEARN LAW EFFECTIVELY (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
Learning law is a complex process that requires both knowledge acquisition and the development of critical cognitive skills. This article presents evidence-based strategies for mastering the law effectively, drawing from cognitive science and educational theory. It emphasizes the importance of active learning techniques such as the case and Socratic methods, spaced repetition for long-term retention, and the contextualization of legal principles. Additionally, it highlights the value of self-testing, feedback, stress management, and collaboration in the learning process. By incorporating these strategies, law students can enhance their understanding, retention, and application of legal knowledge, ultimately preparing them for a successful legal career.